El final del Arcaísmo y la transformación de los mecanismos de intercambio en el Mediterráneo - Domínguez Monedero, Adolfo J. (Gerión. Revista de Historia Antigua, 2010)
The exploratory travel of Democedes of Croton can also be read from the perspectives of the mechanisms of exchange and interaction which are developing in the Mediterranean in the late Archaic Age. This episode serves as a starting point to explore the process of transformation experienced in those moments throughout the Mediterranean by systems of exchange which had converted the emporion in their main tool and the increasing needs for protection and control expressed by the states. The big unrest resulting from the opposing interests of those states will mark the end of an economic model and it shall provoke a series of tensions and wars which will be interpreted in the sources with cross-accusations of piracy.
Keywords: Trade; Emporion; Piracy; Exploratory travels; Democedes of Croton